The Impact of Parenting Patterns in Disciplining Students at Primary School Batanghari Regency - Sulistyaningsih, Dewi (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2021)
This research examines the impact of parenting patterns on student discipline at SDN 110 Tenam, Batanghari Regency. The significance of this research lies in discussing the importance of the role of parents in shaping student behavior and academic achievement. A mixed methods approach was used, combining surveys to collect quantitative data on parenting styles and disciplinary issues, and interviews to gain qualitative insight into parental attitudes and disciplinary strategies. The results showed a correlation between authoritative parenting and positive student discipline outcomes, while authoritarian and permissive parenting styles were associated with higher levels of student discipline problems. In addition, qualitative analysis revealed differences in parents' perceptions and approaches to disciplining children. The novelty of this research lies in its focus on a specific school context and its integration of quantitative and qualitative methodologies. The implications of these findings underscore the importance of encouraging authoritative parenting practices to foster a conducive learning environment and improve student behavior. This research contributes to the broader discourse regarding effective parenting strategies and their impact on student discipline, advocating for collaborative efforts between parents, educators, and policymakers to support holistic student development.